Integrated Bayesian Approaches Shed Light on the Dissemination Routes of the Eurasian Grapevine Germplasm - Mercati, Francesco; De Lorenzis, Gabriella; Mauceri, Antonio; Zerbo, Marcello; Brancadoro, Lucio; D'Onofrio, Claudio; Morcia, Caterina; Barbagallo, Maria Gabriella; Bignami, Cristina; Gardiman, Massimo; de Palma, Laura; Ruffa, Paola; et al. (Frontiers in Plant Science, 2021)
The domestication and spreading of grapevine as well as the gene flow history were debated. We used a high-quality 7k SNP dataset of 1,038 Eurasian grape varieties with unique profiles to assess population genetic diversity, structure and relatedness, and to infer the most likely migration events. Comparisons of putative scenarios of gene flow throughout Europe from Caucasus aided to fit the more reliable migration routes around the Mediterranean Basin. A multiple Bayesian computations approach made possible to lay an ultimate foundation on several questions remained unsolved so far. Firstly, the assessment of genetic diversity and population structure within a well-covering dataset of Italian old varieties suggested the different histories between Northern and Southern Italian grapevines. Moreover, for the first time, Italian genotypes showed to be distinct from all the other Eurasian populations. The entire Eurasian panel confirmed the East-to-West gene flow, highlighting the specific Greece role as a “bridge” between Western and Eastern Eurasia. Portuguese germplasm showed a greater proximity to French than Spanish varieties, accounting as the main route for gene flow from Iberian Peninsula to Central Europe. Finally, our finding reconciled genetic and archaeological data for one of the most cultivated and fascinating crops in the world.